THE EFFECT OF CASH TURNOVER, RECEIVABLES TURNOVER AND INVENTORY TURNOVER ON LIQUIDITY IN CHEMICAL SUBSECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Anis Fuad Salam; Abdurrohman Abdurrohman; Abdul Wahid Alfarizi; Fahmi Amirulloh Anwar (SEAN Institute, 2022)
This study aims to determine whether there is an influence between cash turnover, accounts receivable turnover and inventory turnover on liquidity in chemical subsector companies listed on the Indonesia Stock Exchange either partially or simultaneously. This research was conducted at the Indonesia Stock Exchange with a sample of chemical subsector companies and sampling using a purposive sampling technique. This study uses descriptive analysis, multiple regression analysis, and the classical assumption test which consists of a normality test, multicollinearity test, heteroscedasticity test, and hypothesis testing is done by partial testing (t test), simultaneous test (f test) and the coefficient of determination with a test tool SPSS. The results of research conducted partially show that cash turnover has no significant effect on liquidity; accounts receivable turnover has a significant effect on liquidity; and Inventory turnover has a negative and significant effect on liquidity. While simultaneously cash turnover, accounts receivable turnover and inventory turnover have a significant effect on liquidity